The relationship of domestic pet ownership with the risk of childhood asthma: A systematic review and meta-analysis - Ji, Xiaoyi; Yao, Yuan; Zheng, Ping; Hao, Chuangli (Frontiers in Pediatrics, 2022)
Background and Objective The relationship between pet ownership and childhood asthma remains controversial. In recent years, there have been increasing studies with large sample size. Therefore, we conducted this systematic review and meta-analysis to evaluate the relationship between pet ownership and childhood asthma. Method Relevant research was retrieved from PubMed, Cochrane, EMBASE, and Web of science. The retrieval was as of October 1, 2021. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included studies. Stata 15.0 was used to conduct the meta-analysis. Results A total of 60 studies with large sample size published between 1995 and 2021 were included in this systematic review and meta-analysis, which included 18 cohort studies and 42 case-control studies covering 27 countries and 1,871,295 children. As shown by meta-analysis results, cat ownership (OR = 1.18, 95%CI: 1.05∼1.33) and dog ownership (OR = 1.12, 95%CI: 1.0 0∼1.24) have a significant bearing on the occurrence of childhood asthma. Pet ownership was also positively correlated with the occurrence of severe childhood asthma (OR = 1.15, 95%CI: 1.11∼1.20). Conclusion Pet ownership, especially cats and dogs, is associated with the occurrence of asthma in children.